JUSTICE: RELEVANCE OF THE PROBLEM IN CONTEMPORARY SOCIO-PHILOSOPHICAL DISCOURSE - Федоровська, О. Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The author’s starting point is the idea of justice which can be traced back to Aristotle’s philosophy and ought to underlie contemporary nation-building. Justice is viewed in its synthetic meaning embracing ethical, political, and law aspects. However, a pivotal role of moral justice is emphasized, for the development of social relations system depends primarily on it. Justice as a regulatory category also preconditions individuals’ free activity that is an up-to-date issue in contemporary Ukrainian society. In article substantive provisions of the theory of the justice which has been put forward by John Rawls are considered. The analysis of substantive provisions of this theory, an approach to the problem of philosophers G.L.A. Hart and P. Ricker is considered.